Human biogeography and faunal exploitation in Diamante River basin, central western Argentina - Otaola, Clara (2019)
A biogeographic model used to describe human peopling of southern Mendoza, central western Argentina, proposed an intensification process activated by an increase in population growth rate during the Late Holocene. During this process, high-ranked resources at the surroundings of residential camps were depleted, and hunter–gatherers broadened their diet by incorporating a larger number of low-ranked prey and domesticated plant resources. In this paper, we evaluate an alternative hypothesis, focusing on zooarchaeological data from the Diamante River basin. The results show that faunal resource intensification does not appear to have occurred in the Diamante River basin during the Late Holocene. Faunal consumption in Diamante River basin mainly reflects the local fauna in each ecological zone. The data do not show a lack of higher ranked resources. We suggest it is more likely that the demographic increase was not significant enough to cause an impact on the faunal resources. The archaeological evidence should be improved and analysed in smaller scales to continue with the intensification debate.